2024
DOI: 10.4103/1673-5374.374139
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of taurine as a therapeutic agent for neurological disorders

Abstract: Taurine is a sulfur-containing, semi-essential amino acid that occurs naturally in the body. It alternates between inflammation and oxidative stress-mediated injury in various disease models. As part of its limiting functions, taurine also modulates endoplasmic reticulum stress, Ca 2 + homeostasis, and neuronal activity at the molecular level. Taurine effectively protects against a number of neurological disorders, including stroke, epilepsy, cerebral ischemia, memory dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Taurine is a non-proteinogenic amino sulfonic acid widely distributed in animal tissues and naturally occurs in foods with protein, such as the meat of fish (60)(61)(62)(63). We previously found that marine products (especially, fish) could inhibit HIF activation in ocular cells in vitro and in vivo and further suppress retinal neovascularization in a neonatal murine model of OIR (18).…”
Section: Discussionmentioning
confidence: 99%
“…Taurine is a non-proteinogenic amino sulfonic acid widely distributed in animal tissues and naturally occurs in foods with protein, such as the meat of fish (60)(61)(62)(63). We previously found that marine products (especially, fish) could inhibit HIF activation in ocular cells in vitro and in vivo and further suppress retinal neovascularization in a neonatal murine model of OIR (18).…”
Section: Discussionmentioning
confidence: 99%
“…In this explanation, the significance of the olive polyphenol modulation of Nrf2-related stress-responsive genes, which, in accordance with the hormesis theory, activate this neuroprotective cascade to maintain brain health, was highlighted, as well as offering potential application in the prevention and treatment of aging and age-related cognitive disorders in people [32,33]. Moreover, some other natural compounds, such as geraniol, soyasapogenol-B, taurine, and nobiletin, showed promising results for the management of neurological manifestations [13,30,34,35]. Similar to natural products, works have shown the therapeutic potential of the use of fungal metabolites against various disorders [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous therapeutic benefits of organic substances and nanoparticles have been described in the past to regulate the negative pathophysiological consequences associated with oxidative stress, infection by microbes, gastric ulcer, hypercholesterolemia, cancer and brain diseases [19][20][21][22][23][24][25][26][27][28][29] . Several reports suggested their beneficial role for neurological disorders, tumours, and other diseases [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] .…”
Section: Introductionmentioning
confidence: 99%